Therapeutic Potential of Glucose Oxidase-Loaded Biogenic Mesoporous Silica Nanoparticles in Ovarian Cancer - Andrea G. Uriostegui-Pena; Padmavati Sahare; Gabriel Luna-Bárcenas; Sujay Paul (Pharmaceuticals)
Background/Objectives: Ovarian cancer (OC) remains one of the most lethal malignancies of the female reproductive system. Glucose oxidase (GOx) has emerged as a potential therapeutic agent in cancer treatment by inducing tumor starvation through glucose depletion. Nonetheless, its clinical application is constrained due to its systemic toxicity, immunogenicity, poor in vivo stability, and short half-life. These challenges can be addressed through nanotechnology; in particular, biogenic mesoporous silica nanoparticles (MSNs) offer promise as drug delivery systems (DDSs) that enhance therapeutic efficacy while minimizing side effects. Methods: Biogenic MSNs were extracted from the Equisetum myriochaetum plant via acid digestion, functionalized with 3-aminopropiltrietoxysilane (APTES) and glutaraldehyde (GTA), and loaded with GOx. The free and immobilized MSNs were characterized using FTIR, DLS, XRD, SEM/EDX, and BET techniques. A colorimetric approach was employed to quantify the enzymatic activity of both the free and immobilized GOx. The MTT assay was employed to assess the viability of SKOV3 cells. The obtained IC50 concentration of the nanoformulation was administered to SKOV3 cells to analyze the expression of cancer-related genes using RT-qPCR. Results: IC50 values of 60.77 ng/mL and 111.6 µg/mL were ascertained for the free and immobilized GOx, respectively. Moreover, a significant downregulation of the oncogene β-catenin (CTNNB1) was detected after 24 h with the nanoformulation. Conclusions: Our findings indicate that GOx-loaded biogenic MSNs may serve as a potential therapeutic agent for ovarian cancer. This is, to the best of our knowledge, the first report exploring the effect of GOx-loaded biogenic MSNs on SKOV3 cells.